Serum Uric Acid Is Associated with Poor Outcome in Black Africans in the Acute Phase of Stroke - Yacouba N. Mapoure; Chia Mark Ayeah; M. S. Doualla; H. Ba; Hugo B. Mbatchou Ngahane; Salomon Mbahe; Henry N. Luma (Stroke Research and Treatment)
Background. Prognostic significance of serum uric acid (SUA) in acute stroke still remains controversial. Objectives. To determine the prevalence of hyperuricemia and its association with outcome of stroke patients in the Douala General Hospital (DGH). Methods. This was a hospital based prospective cohort study which included acute stroke patients with baseline SUA levels and 3-month poststroke follow-up data. Associations between high SUA levels and stroke outcomes were analyzed using multiple logistic regression and survival analysis (Cox regression and Kaplan-Meier). Results. A total of 701 acute stroke patients were included and the prevalence of hyperuricemia was 46.6% with a mean SUA level of 68.625 ± 24 mg/l. Elevated SUA after stroke was associated with death (OR = 2.067; 95% CI: 1.449–2.950; p < 0.001) but did not predict this issue. However, an independent association between increasing SUA concentration and mortality was noted in a Cox proportional hazards regression model (adjusted HR = 1.740; 95% CI: 1.305–2.320; p < 0.001). Furthermore, hyperuricemia was an independent predictor of poor functional outcome within 3 months after stroke (OR = 2.482; 95% CI: 1.399–4.404; p = 0.002). Conclusion. The prevalence of hyperuricemia in black African stroke patients is quite high and still remains a predictor of poor outcome.